Experimental results applying second order sliding mode control to a PEM fuel cell based system - Kunusch, Cristian (2013)
A robust control solution is proposed to solve the air supply control problem in autonomous polymer electrolyte membrane fuel cells (PEMFC) based systems. A Super Twisting controller is designed using a nonlinear model of a laboratory fuel cell test station, even a Lyapunov based stability discussion is included. Subsequently, the proposed control strategy is successfully implemented in the laboratory test bench. Highly satisfactory results are obtained, regarding dynamic behaviour, oxygen stoichiometry regulation and robustness against uncertainty.